Effect of Vitamin-D supplementation in adults presenting with chronic lower back pain - Rahman Rasool Akhtar , Riaz Ahmed , Sabeen Ashraf , Omair Ashraf , Umer Shafique , Ayesha Mureed, (Journal of Rawalpindi Medical College, 2020)
Background: Chronic pain in the lower back of adults is a common problem and mostly associated with Vitamin D deficiency. Along with standard treatment, vitamin D supplementation can help in early and better relief from back pain. Objective: To assess the effectiveness of vitamin D supplementation in patients with chronic lower back pain. Study Design & Methods: This Quasi-experimental trial was conducted at Department of Orthopaedics, Benazir Bhutto Hospital for 6 months. The patients aged between 15 to 55 years with chronic low back pain were included and pain score was noted by using a visual analogue scale (VAS). Patients were prescribed with oral vitamin D3 with a dose of 50,000 IU weekly for eight weeks (induction phase) and oral vitamin D3 with a dose of 50,000 IU once monthly for 6 months (maintenance phase). Outcome parameters included pain measured by VAS, functional disability by modified Oswestry disability questionnaire scores, and Vitamin-D3 levels at baseline,2, 3 and 6 months post-supplementation. Results: Mean age of patients was 44.21± 11.92 years.There were 337 (56.2%) male patients while 263 (43.8%) female patients. Baseline mean vitamin-D levels were 13.32 ± 6.10 ng/mL and increased to 37.18 ± 11.72 post supplementation (P < 0.0001). There was a significant decrease in the pain score after 2nd, 3rd& 6th months (61.7 ± 4.8, 45.2 ± 4.6 & 36.9 ± 7.9, respectively) than 81.2 ± 2.4 before supplementation (P < 0.001). The modified Oswestry disability score also showed significant improvement after 2nd, 3rd& 6thmonths (35.5 ± 11.4, 30.2 ± 9.4 & 25.8 ± 10.6, respectively) as compared to baseline 46.4 ± 13.2 (P < 0.001). About 418 (69.7%) patients attained normal levels after 6 months. Conclusion: Prescription of Vitamin D in addition to standard therapy for chronic lower back pain can be beneficial in getting relief from pain and improving the functional ability of the patient.